Cardiac anatomy, function and metabolism in elite cyclists assessed by magnetic resonance imaging and spectroscopy - Pluim, B. M.; Chin, J. C.; de Roos, A.; Doornbos, J.; Siebelink, H. M.; van der Laarse, A.; Vliegen, H. W.; Lamerichs, R. M.; Bruschke, A. V.; van der Wall, E. E. (European Heart Journal, 1996)
We investigated whether left ventricular hypertrophy in elite cyclists is associated with functional changes or abnormal energy metabolism. Left ventricular hypertrophy is a powerful risk factor for sudden cardiac death with different prognostic significance among the various geometric forms. Cyclists may have a combination of mixed eccentric and concentric hypertrophy. Magnetic resonance imaging was used to define left ventricular mass, geometry and function. Thirteen highly trained male cyclists and 12 healthy controls were investigated. Proton-decoupled phosphorus-31 cardiac spectroscopy was performed to assess parameters of myocardial high-energy phosphate metabolism. Left ventricular mass and end-diastolic volumes normalized for body surface area were significantly higher in cyclists (124.1 +/- 9.4 g.m-2 and 106.2 +/- 11.4 ml.m-2, respectively) than in controls (85.9 +/- 9.3 g.m-2 and 79.1 +/- 11.6 ml.m-2, respectively), (both P < 0.0001). The left ventricular mass to end-diastolic volume ratio, as a parameter of left ventricular geometry, was not significantly increased in cyclists compared to controls. Resting left ventricular ejection fraction, cardiac index, and systolic wall stress in cyclists did not differ significantly from those of controls. The phosphocreatine to adenosine triphosphate ratio was not significantly different between cyclists and controls (2.2 +/- 0.34 vs 2.2 +/- 0.17, ns). Cyclists show prominent left ventricular hypertrophy with normal geometry. The finding that the hypertrophic hearts of the cyclists had normal left ventricular function and a normal phosphocreatine to adenosine triphosphate ratio suggests that sport-induced left ventricular hypertrophy is a physiological adaptation rather than a pathophysiological response.